EFEKTIVITAS EVALUASI PEMBELAJARAN DALAM MENGUKUR CAPAIAN KOMPETENSI PESERTA DIDIK - Karis Karis; Barokah Isdaryanti; Wiwi Isnaeni (STKIP Subang, 2026)
Evaluation of learning plays a strategic role in determining the achievement of students' competencies. Appropriate evaluation not only measures learning outcomes but also provides information regarding students' cognitive, affective, and psychomotor development. This study aims to analyze the effectiveness of learning evaluation in measuring students' competency achievement in the learning process. The study employed a qualitative descriptive approach through literature review by examining various scientific publications, educational policy documents, and previous research related to learning evaluation. The findings indicate that effective learning evaluation must fulfill the principles of validity, reliability, objectivity, continuity, and comprehensiveness. Various evaluation techniques, including formative assessment, summative assessment, authentic assessment, performance assessment, portfolio assessment, and project-based assessment, provide a more comprehensive picture of students' competency achievement than conventional written tests. In addition, evaluation results function as the basis for improving learning quality, determining follow-up actions, and enhancing teachers' instructional strategies. Therefore, implementing comprehensive and competency-based learning evaluation contributes significantly to improving educational quality and developing students' competencies according to the objectives of the Independent Curriculum.